2008
DOI: 10.1177/1363459308090054
|View full text |Cite
|
Sign up to set email alerts
|

Persons with acquired profound hearing loss (APHL): how do they and their families adapt to the challenge?

Abstract: a b s t r a c t The study examined the impact of acquired profound hearing loss (APHL) on the relationship between the hearing impaired person and their normally hearing close family member, usually a partner, and identifi ed the kinds of adjustment leading to maintenance or deterioration of the relationship. The participants were 25 people with APHL and 25 family members, interviewed separately in their own home. Analysis of the interview transcripts adopted a grounded theory methodology. The different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…(16) What are the most positive changes you have experienced with the implant? (17) What are the most negative experiences with the implant?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) What are the most positive changes you have experienced with the implant? (17) What are the most negative experiences with the implant?…”
Section: Resultsmentioning
confidence: 99%
“…Even if the effects of severe to profound HI on significant others have been recognized [15][16][17], there is a limited number of previous studies examining this issue in relation to CI-users. In an evaluation of outcomes of CI in children, Archbold et al [18] used a questionnaire with the aim to capture the parental perspective of CI in children.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily hearing loss affects social interaction and relationships and manifests itself as a communication loss between the person with hearing loss (PHL) and communication partners (CPs) in addition to other types of psychosocial problems. [18][19][20][21][22] The Encounter Model suggests that hearing loss and its management cannot be separated from the broader circumstances of a patient's life, including the patient's social reality. Consequently, broadening our understanding of the patient's perspective to include the social context can in fact help audiologists better interpret patient behavior, noncompliance, and motivation for the audiological recommendations we make.…”
Section: The Patient's Perspectivementioning
confidence: 99%
“…In fact, this research has shown that both the PHLs and CPs are affected in different ways by hearing loss. [18][19][20][21][22] The question of whether a CP's well-being can be influenced by communication loss is an important one for audiologists to consider. The World Health Organization's International Classification of Functioning, Disability, and Health 23 provides a framework for describing consequences of health conditions on daily functioning.…”
Section: The Patient's Perspectivementioning
confidence: 99%
“…[2][3][4] As hearing loss is one of the most prevalent of chronic conditions, the presence and utilization of social support structures can have a positive influence on its management. The presence of hearing loss affects the spouse or significant other in some positive 5 but largely negative [6][7][8][9][10] ways. In many cases, it is the presence of a significant other that motivates a person with hearing loss to seek help, thereby becoming a crucial component of the rehabilitation processs.…”
mentioning
confidence: 99%